Detection of Pb(II): Au Nanoparticle Incorporated CuBTC MOFs - Gajanan A. Bodkhe; Bhavna S. Hedau; Megha A. Deshmukh; Harshada K. Patil; Sumedh M. Shirsat; Devdatta M. Phase; Krishan K. Pandey; Mahendra D. Shirsat (Frontiers in Chemistry, 2020)
In the present investigation, copper benzene tricarboxylate metal organic frameworks (CuBTC MOF) and Au nanoparticle incorporated CuBTC MOF (Au@CuBTC) were synthesized by the conventional solvothermal method in a round bottom flask at 105°C and kept in an oil bath. The synthesized CuBTC MOF and Au@CuBTC MOFs were characterized by structure using X-ray diffraction (XRD) spectroscopic methods including Fourier Transform Infrared spectroscopy, Raman Spectroscopy, X-ray Photoelectron Spectroscopy (XPS), and Energy dispersive spectroscopy (EDS). We also characterized them using morphological techniques such as Field emission scanning electron microscopy (FE-SEM), and electrochemical approaches that included cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). We examined thermal stability by thermogravimetric analysis (TG/DTA) and N2 adsorption—desorption isotherm by Brunauer-Emmett-Teller (BET) surface area method. Both materials were tested for the detection of lead (II) ions in aqueous media. Au nanoparticle incorporated CuBTC MOF showed great affinity and selectivity toward Pb2+ ions and achieved a lower detection limit (LOD) of 1 nM/L by differential pulse voltammetry (DPV) technique, which is far below than MCL for Pb2+ ions (0.03 μM/L) suggested by the United States (U.S.) Environmental Protection Agency (EPA) drinking water regulations.